2019
DOI: 10.3390/molecules24193445
|View full text |Cite
|
Sign up to set email alerts
|

Quickly Identifying High-Risk Variables of Ultrasonic Extraction Oil from Multi-Dimensional Risk Variable Patterns and a Comparative Evaluation of Different Extraction Methods on the Quality of Forsythia suspensa Seed Oil

Abstract: Generally, essential oils and components of interest are extracted from plants using organic solvent, distillation, ultrasound and supercritical extraction methods. Ultrasonic extraction (UE) has the advantage of high efficiency, but its process is complicated and it has numerous variables. In this study, an L18-Hunter experimental design was applied for the first time to investigate the practicability of applying UE to Forsythia suspensa seed oil. Six potential high-risk variables, including numerical and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…The broad band ranging from 3300 to 3200 cm − 1 correspond to the stretch vibration of OH groups of alcoholic and phenolic compounds [36]. The picks located in the region around 2988-2850 cm − 1 are assigned for CH stretching including CH, CH 2 and CH 3 bending vibrations possibly derived from carbohydrates [37].…”
Section: Extraction Yields and Phenolic Contentmentioning
confidence: 99%
“…The broad band ranging from 3300 to 3200 cm − 1 correspond to the stretch vibration of OH groups of alcoholic and phenolic compounds [36]. The picks located in the region around 2988-2850 cm − 1 are assigned for CH stretching including CH, CH 2 and CH 3 bending vibrations possibly derived from carbohydrates [37].…”
Section: Extraction Yields and Phenolic Contentmentioning
confidence: 99%
“…Em sementes de Forsythia suspensa a extração com ultrassom foi mais eficiente que métodos envolvendo fluido supercrítico, hidrodestilação e soxhlet, apresentando benefícios e aplicação em indústria de alimentos (Ming et al, 2019). A extração de compostos de Baccharis dracunculifolia por ultrassom, permite a obtenção de forma sustentável com potencial para indústria de alimentos e de cosméticos (CAVALARO et al, 2020).…”
Section: Extração De Compostos Utilizando Ultrassomunclassified
“…Equation (1) revealed that factor A positively impacted Y 1 , while the other two factors (C and F) had a negative impact. Equation (2) revealed that all factors (A, C, and F) had a negative impact on Y 2 .…”
Section: Plackett-burman Design (Pbd) Studymentioning
confidence: 99%
“…EOs have been widely used in the pharmaceutical, cosmeceutical, and food industries for their various biological activities, including antioxidant, anti-inflammatory, antibacterial, sedative, antiparasitic, spasmolytic analgesic activities, etc. [1][2][3][4]. It has been shown that EOs contain different kinds of bioactive compounds, particularly phenolic-derived aromatics and terpenes [5].…”
Section: Introductionmentioning
confidence: 99%